Faktor-Faktor Yang Mempengaruhi Perilaku Konsumen Terhadap Keputusan Pembelian Bunga Potong Krisan (Studi Kasus: Desa Bulukerto, Kecamatan Bumiaji, Kota Batu) - Jeckslin Manao, Leo; Triwulan Budisaptorini, Anasthasia; Pungky D.H, Johanes (BiSTeK Pertanian, 2024)
Ornamental plants are horticultural plants that have the potential to be developed in Indonesia, namely Chrysanthemum Cut Flowers. Horticultural crops are divided into two namely edible plants and non-edible plants. This study aims to analyze the effect of color quality, shape quality, location, means of place of purchase and consumer income influencing the decision to purchase cut flowers in Bulukerto Village, Bumiaji District, Batu City. This research was conducted in Bulukerto Village, Bumiaji District, Batu City. The determination of the sample in this study was accidental sampling, the population in this study was 30 people. Data was collected using a questionnaire given to consumers who bought chrysanthemum cut flowers directly. The analytical tool used is multiple linear regression analysis using determination test, F test (simultaneous), t test (partial). The results showed that what influenced the purchasing decision of chrysanthemum cut flowers, namely color quality (X1), shape quality (X2), location (X3), means of place of purchase (X4) and consumer income (X5) simultaneously significantly affected the dependent variable (Y). Variables that partially have a significant effect are location, means of place of purchase, and consumer income. While the color quality and shape quality variables have no significant effect on the number of purchases.